2019
DOI: 10.1080/00207454.2018.1543670
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of mechanistic insights of Aβ42 interactions against extracellular domain of nAChRα7 in Alzheimer’s disease

Abstract: Aim: Amyloid beta (Ab) 1-42, which is a basic constituent of amyloid plaques, binds with extracellular transmembrane receptor nicotine acetylcholine receptor a7 (nAChRa7) in Alzheimer's disease. Materials and Methods: In the current study, a computational approach was employed to explore the active binding sites of nAChRa7 through Ab 1-42 interactions and their involvement in the activation of downstream signalling pathways. Sequential and structural analyses were performed on the extracellular part of nAChRa7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Recent reports have shown the direct interactions between α7 receptors and Aβ 42 [ 23 , 24 , 25 ]. These studies strongly suggest that the α7 receptor can contribute to synaptic dysfunction in ‘Alzheimer’s disease (AD) as Aβ oligomers can alter neuronal signalling through interactions with nicotinic receptors, particularly with α7.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown the direct interactions between α7 receptors and Aβ 42 [ 23 , 24 , 25 ]. These studies strongly suggest that the α7 receptor can contribute to synaptic dysfunction in ‘Alzheimer’s disease (AD) as Aβ oligomers can alter neuronal signalling through interactions with nicotinic receptors, particularly with α7.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is a computational approach used to predict the binding conformational behavior of biomolecules, i.e., drugs and proteins. All of the screened drugs were docked and analyzed based on binding affinity (kcal/mol) (see the Supplementary Data S2). From docking results, it has been observed that from 100 FDA-approved drugs, 24 drugs showed binding affinity values higher than −7 kcal/mol and may have good binding potential inside the binding pocket of the EWS protein.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Protein interactions initiate the downstream signaling pathways and are involved in the occurance of neurological diseases 57 , 58 . The decreased flexibility of protein backbone is considered a major hallmark for checking the stability of docked complexes using MD simulation 56 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%